Dominantly inherited Alzheimer's disease in Latin America: Genetic heterogeneity and clinical phenotypes. Issue 4 (23rd November 2020) - Llibre‐Guerra, Jorge J.; Li, Yan; Allegri, Ricardo F.; Mendez, Patricio Chrem; Surace, Ezequiel I.; Llibre‐Rodriguez, Juan J.; Sosa, Ana Luisa; Aláez‐Verson, Carmen; Longoria, Erika‐Mariana; Tellez, Alberto; Carrillo‐Sánchez, Karol; Flores‐Lagunes, Luis Leonardo; et al.
Abstract: Introduction: A growing number of dominantly inherited Alzheimer's disease (DIAD) cases have become known in Latin American (LatAm) in recent years. However, questions regarding mutation distribution and frequency by country remain open. Methods: A literature review was completed aimed to provide estimates for DIAD pathogenic variants in the LatAm population. The search strategies were established using a combination of standardized terms for DIAD and LatAm. Results: Twenty‐four DIAD pathogenic variants have been reported in LatAm countries. Our combined dataset included 3583 individuals at risk; countries with highest DIAD frequencies were Colombia (n = 1905), Puerto Rico (n = 672), and Mexico (n = 463), usually attributable to founder effects. We found relatively few reports with extensive documentation on biomarker profiles and disease progression. Discussion: Future DIAD studies will be required in LatAm, albeit with a more systematic approach to include fluid biomarker and imaging studies. Regional efforts are under way to extend the DIAD observational studies and clinical trials to Latin America.